Modelos de predição de exigencias nutricionais de codornas japonesas nas fases inicial e crescimento - Oliveira, Everton Jose do Nascimento (Universidade Federal do Tocantins, 2021)
This work was carried out in the Coturniculture Sector of the Federal University of Tocantins - Campus de Araguaína with the objective of determining the energy and protein requirements for Japanese quails through the factorial method of estimating nutritional predictions separating the components of maintenance, gain and production for the initial and growth phases. The thesis was distributed in three chapters: Theoretical framework (1). Energy requirements through mathematical models for maintenance and weight gain of Japanese quails from 01 to 35 days old (2). Crude protein requirements through mathematical models for maintenance and weight gain of Japanese quails from 01 to 35 days old (3). The initial phase was from 01 to 15 and the growth from 15 to 35 days of age with maintenance estimates being determined in cage-type rearing systems in a natural environment, with an average temperature of 24.05ºC, using the methodology comparative slaughter, by means of feeding test for both phases. A completely randomized design was used with four treatments (ad libitum, 75, 50 and 25% of ad libitum consumption), six replicates and ten birds per cage. The maintenance requirements were estimated by the intercept of the line with the X axis, considering the retentions as a function of energy and/or protein consumption, respectively. As for the estimates of weight gain requirements, a group of 75 birds in the initial phase and 40 for the growth phase were created on the shavings covered floor alongside the maintenance birds, fed at will and housed at an ambient temperature of 24, 05ºC and 15 birds slaughtered at 3, 6, 9, 12 and 15 days of age and 10 birds at 20, 25, 30 and 35 days respectively for the initial and growing phases. The prediction equations to estimate the requirements for maintenance and weight gain in energy and protein of Japanese quails in the period from 01 to 15 and 15 to 35 days of age were respectively: AME (1–15d) = (54.96 × W0.67 ) + (8.30 × WG) and AME (15-35d) = (92.11 × W0.67) + (8.91 × WG) and CP (1-15d) = (2.095 × W0.67) + (0.851 × WG) and CP (15-35d) = (6.30 × W0.67) + (0.894 × WG), where AME is the apparent metabolizable energy requirement, CP is the crude protein requirement , WG is the weight gain (g/bird/d) and W is the body weight (kg).